Low Carbohydrate Diets and Estimated Cardiovascular and Metabolic Syndrome Risk in Prostate Cancer. Issue 6 (14th December 2021) - Freedland, Stephen J.; Howard, Lauren E.; Ngo, Alexis; Ramirez-Torres, Adela; Csizmadi, Ilona; Cheng, Susan; Mack, Alexandra; Lin, Pao-Hwa
Abstract : Purpose: A low carbohydrate diet (LCD) was shown to suggestively slow prostate cancer (PC) growth. In noncancer patients, LCDs improve metabolic syndrome (MetS) without weight loss. However, concerns about negative impact on cardiovascular disease (CVD) risk remain. The objective of this secondary analysis is to determine the impact of an LCD on risk of MetS and estimated CVD risk in patients with PC. Materials and Methods: Pooled data were analyzed from 2 randomized trials testing LCD vs control on 1) preventing insulin resistance after starting hormone therapy (CAPS1) and 2) slowing PC growth in recurrent PC after failed primary treatment (CAPS2). Both trials included a usual care control vs LCD intervention in which patients were instructed to limit carbohydrate intake to ≤20 gm/day, and in CAPS1 only, to walk for ≥30 minutes/day for ≥5 days/week. MetS components (hypertension, high triglycerides, low high-density lipoprotein cholesterol, central obesity and diabetes), 10-year CVD risk estimated using the Framingham Score with either body mass index (BMI) or lipids, and remnant cholesterol were compared between arms using mixed models adjusting for trial. Results: LCD resulted in a significantly reduced risk of MetS (p=0.004) and remnant cholesterol (p <0.001). Moreover, LCD resulted in significantly lower estimated CVD risk using BMI (p=0.002) over the study with no difference in estimated CVD risk using lipids (p=0.14). Conclusions: LCD resulted in a significantly reduced risk of MetS and remnant cholesterol, and a significantly lower estimated CVD risk using BMI. By comparison, there was no difference in estimated CVD risk using lipids. Study limitations include small sample size, short followup, and inability to distinguish effects of carbohydrate restriction and weight loss. Long-term studies are needed to confirm this finding.